If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (32 + x) + -10 = 3x Remove parenthesis around (32 + x) 32 + x + -10 = 3x Reorder the terms: 32 + -10 + x = 3x Combine like terms: 32 + -10 = 22 22 + x = 3x Solving 22 + x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 22 + x + -3x = 3x + -3x Combine like terms: x + -3x = -2x 22 + -2x = 3x + -3x Combine like terms: 3x + -3x = 0 22 + -2x = 0 Add '-22' to each side of the equation. 22 + -22 + -2x = 0 + -22 Combine like terms: 22 + -22 = 0 0 + -2x = 0 + -22 -2x = 0 + -22 Combine like terms: 0 + -22 = -22 -2x = -22 Divide each side by '-2'. x = 11 Simplifying x = 11
| 50=5000/12*r | | 2=14-2h | | (-2+3a)/(9a^2-4) | | 4x-x+5=3x-9 | | 10x+90=100 | | 95=6000/12*r | | 4=31-9t | | 6(x+2)=2(3x+2)+8 | | 0.4(2-x)-(x+3)= | | 7x/3/8=6x-5/8 | | t+1/2=2t-3/6 | | 2=56-9t | | -35+4/15 | | 13x+30=23x-15 | | 0.35s+0.6(30-s)=0.45(30) | | 26-9x=3x-1 | | 9-6x/7=16 | | 12(3x+3)-7(2x-6)=2x-42 | | 6-3x-5x-10x+18-12= | | p-16=51 | | -7/2*10 | | 2(5x-3)-2x-4=5-(6x+1) | | -9-6x/7=16 | | 0.20x+0.05(10-x)=0.10(14) | | -27=n-20 | | 14-3(x-2)=x+16 | | 2a+7=50 | | -7/2-1/4 | | -7/10t=1/8 | | (43-7x)+(83-11x)=(117-22x) | | x^2-12x-16=0 | | c+160=1780 |